2020
DOI: 10.1007/s42729-020-00240-y
|View full text |Cite
|
Sign up to set email alerts
|

Economically Optimal Rate for Nutrient Application to Maize in the Semi-deciduous Forest Zone of Ghana

Abstract: Low inherent nitrogen (N), phosphorus (P), and potassium (K) contents of smallholder farms limit maize grain yield. Maize grain yield response to N, P, and K mineral fertilizer application and economically optimal rates for nitrogen (EOR N), phosphorus (EOR P), and potassium (EOR K) were evaluated on a Ferric Acrisol within the semi-deciduous forest zone of Ghana. The nutrient rates evaluated were N (0, 30, 60, 90, and 120 kg N ha −1), P (0, 30, 60, and 90 kg ha −1 P 2 O 5), and K (0, 30, 60 and 90 kg ha −1 K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Even though the residual effect of the treatment on maize was not significant, the yields produced were comparable to yields obtained under mineral and organic fertilizer trials ( Essel et al, 2020 ) and about double the current national average yield of 2.26 t ha −1 ( Ministry of Food & Agriculture, 2018 ). This indicates that the yield cannot be attributed to the treatment effects alone.…”
Section: Discussionmentioning
confidence: 64%
“…Even though the residual effect of the treatment on maize was not significant, the yields produced were comparable to yields obtained under mineral and organic fertilizer trials ( Essel et al, 2020 ) and about double the current national average yield of 2.26 t ha −1 ( Ministry of Food & Agriculture, 2018 ). This indicates that the yield cannot be attributed to the treatment effects alone.…”
Section: Discussionmentioning
confidence: 64%
“…In the present case study, located in eastern Lombardy (Italy), maize production is experiencing relevant variability, being caused mainly by the low price on the market and pest control regulations and limits, which results in increased imports from countries outside the EU [31]. It was observed that dairy farmers hardly adhere to the organic recommended fertilizer application rates due to the high availability of manure and slurry [28,[32][33][34][35][36]; however, to ensure high crop yields, topdressing mineral N is used despite the purchase and environmental costs [37]. Even considering the current subsidized rates, mineral fertilizers still represent a substantial budget item in European farms [38].…”
Section: Introductionmentioning
confidence: 83%
“…An important factor for increasing the efficiency of zero-till technology is an optimization of plant nutrition [25][26][27][28][29]. The balanced fertilization implies that crops are adequately supplied with nutrients at every stage of growth and development.…”
Section: Introductionmentioning
confidence: 99%